REBOA is Here to Stay: How to Manage the Resulting Complications - Lauve, Sarah; Alfonzo, Sabrina Yu; Choi, Kevin; Dies, Ross; Sethi, Danielle; Williams, Lizzie; Sheahan, Claudie; Sheahan, Malachi (Seminars in Interventional Radiology, 2025)
Resuscitative endovascular balloon occlusion of the aorta (REBOA) has emerged as a critical adjunct in the management of trauma-related shock, serving as a temporizing measure to preserve vital organ perfusion and allow time to achieve definitive hemorrhagic control. However, the increasing adoption of REBOA into clinical practice is associated with a spectrum of potential complications that significantly increase morbidity and mortality in the setting of acute traumatic injury. There is little existing research to guide clinical decision-making and monitoring for these feared complications, especially iatrogenic vascular injuries. This paper synthesizes the current evidence on the classification, frequency, and management of vascular complications following REBOA insertion in the setting of trauma in addition to our observations and experiences as a level I trauma center.
Keywords: REBOA; complication; vascular surgery; interventional radiology; trauma